Molecular Mechanisms of Action of Genistein in Cancer: Recent Advances - Hardeep Singh Tuli (Frontiers in Pharmacology, 2019)
Background: Genistein is one among the several other known isoflavones that is found in different soybeans and soy products. The chemical name of genistein is 4′,5,7-trihydroxyisoflavone. Genistein has drawn attention of scientific community because of its potential beneficial effects on human grave diseases, such as cancer. Mechanistic insight of genistein reveals its potential for apoptotic induction, cell cycle arrest, as well as antiangiogenic, antimetastatic, and anti-inflammatory effects.Objective: The purpose of this review is to unravel and analyze various molecular mechanisms of genistein in diverse cancer models.Data sources: English language literature was searched using various databases, such as PubMed, ScienceDirect, EBOSCOhost, Scopus, Web of Science, and Cochrane Library. Key words used in various combinations included genistein, cancer, anticancer, molecular mechanisms prevention, treatment, in vivo, in vitro, and clinical studies.Study selection: Study selection was carried out strictly in accordance with the statement of Preferred Reporting Items for Systematic Reviews and Meta-analyses.Data extraction: Four authors independently carried out the extraction of articles.Data synthesis: One hundred one papers were found suitable for use in this review.Conclusion: This review covers various molecular interactions of genistein with various cellular targets in cancer models. It will help the scientific community understand genistein and cancer biology and will provoke them to design novel therapeutic strategies.